O discurso anticomunista no projeto de supremacia branca: um estudo sobre Lothrop Stoddard e a Ku Llux Klan - Penha, Eros Viana de Lima (2021)
This research has as it’s objetcive to elucidate the relations between the historic anticommunism and the historic racism in the society of the United States, from the narrative of the most infamous of the groups proponents of white supremacy, the Ku Klux Klan, specially from the works that one of it’s most influent “inelectuals”, Lothrop Stoddard, produced